Iran : l’État islamique entre structures monopolistiques et modèle de l’État social - Azadeh Kian-Thiébaut (Revue des Mondes Musulmans et de la Méditerranée)
In post-revolutionary Iran, society has been increasingly fragmented, the economy has remained rentier, and the privatized State has primarily catered to the interests of monopolistic structures that came to life at the creation of revolutionary foundations and as a result of the nationalization of the economy and its re-orientation towards the redistribution sector. The foundations led by conservatives, enjoy an autonomous status, and control an important part of the country’s GDP. Moreover, they are very influential in the political sphere and have until now prevented substantial structural reforms that would entail significant loss to them, although the State-led economy of the 1980’s has evolved towards a market economy.Faced with economic crises and massive unemployment, the government, increasingly preoccupied with the deteriorating social cohesion, approaches the model of the social state by implementing a social policy funded by oil revenues rather than taxation and solidarity. This might impede people’s autonomization from the State, thereby lessening their influence on the State.However, members of the emerging civil society, especially middle classes, are increasingly engaged in social activities through both traditional and modern solidarity networks. They are confronted with a locked political system and are motivated by social participation that would bring changes from below. This social participation is likely to provide the necessary conditions for the development of spheres of social autonomy in the future.